Effect of Container Size on Seedling Growth of Acacia nilotica Ssp. Indica - Venkatesh, A.; Vanangamudi, K.; Umarani, R. (Indian Forester, 2002)
The results revealed that the size of the container has profound influence on Acacia nilotica subsp. indica seedlings' morphometric parameters , viz. , seedling length , shoot collar diameter and total dry weight throughout the growth period of the seedlings. The container of 15 x 20 cm size registered superiority over 10 x 15 cm size polythene containers and the seedlings grown in the nursery bed for all the above growth characteristics of the seedlings.